Crack Growth Monitoring in Stainless Steels by Means of TSA Technique. (2015) - Ancona, F.; De Finis, R.; Palumbo, D.; Galietti, U.
Abstract: In this work, the Thermoelastic Stress Analysis (TSA) technique was used for the monitoring of fatigue crack growth during fracture mechanics tests on stainless steel. In this regards, different methods are used in literature but most of them cannot be applied on real components since they require an off-line measurement of the crack. An automatic procedure based on TSA technique was proposed for the continuous evaluation of the crack tip position. Advantages with respect to classical methods can be obtained in terms of reduction of testing time, experimental set-up, data processing and data report.